Effects of Taxes on Consumer Behavior: A Macro-Economic Study - Rahman, Yusuf (Manunggal Halim Jaya, 2023)
This study investigates the effects of taxes on consumer behavior within the framework of macroeconomics, aiming to provide insights into the intricate relationship between taxation policies and individual choices. Employing a qualitative research approach, the study conducts a comprehensive literature review, drawing on diverse sources such as scholarly articles, books, and reports. Thematic analysis is employed as the primary method for data analysis, allowing for the identification of recurrent patterns and themes across the literature. The research findings reveal that taxes exert a significant influence on consumption patterns, savings behavior, and overall economic activity. Specifically, empirical evidence highlights the effectiveness of excise taxes in shaping consumption behaviors, particularly regarding products like cigarettes and alcohol. Moreover, the incidence of taxation, whether borne by consumers or producers, varies across different product categories and income groups, necessitating careful consideration in tax policy design. The study also underscores the importance of incorporating behavioral insights into tax policy formulation to enhance compliance and minimize evasion. Additionally, the globalization of markets and advancements in technology present new challenges and opportunities for policymakers in navigating the tax-consumer behavior nexus. Addressing these challenges requires innovative approaches and international cooperation to ensure a level playing field between traditional and digital businesses. Overall, the research contributes to a deeper understanding of how taxation policies influence consumer behavior and provides valuable insights for policymakers, businesses, and researchers.